Exploring learners’ perceptions of psychosocial support services in educational institutions: A qualitative Study - Olatunbosun, Stella; Jacob, Udeme; Pillay, Jace (Edelweiss Applied Science and Technology, 2024)
The significance of psychosocial support in educational institutions has garnered attention for its impact on learners’ academic success and well-being. This study explores learners’ perceptions of psychosocial support services in educational settings and their influence on academic performance and mental health. Utilising a qualitative research design, this study engaged participants through semi-structured interviews and focus groups to gather in-depth insights. A purposive sampling method was used to select eight learners (M =3; F =5; Mean age 18 SD = 2.05) from various educational institutions who had accessed psychosocial support services. Thematic analysis was employed to analyse the data, identifying key themes related to the perceptions and effectiveness of the support received. The findings reveal positive perceptions of psychosocial support services among learners, highlighting the importance of personalised support that considers individual needs. Participants noted improved academic performance, self-efficacy, and overall mental health. However, the study also identified areas for improvement, including increased accessibility and awareness of available services. The study underscores the vital role of psychosocial support services in enhancing learners’ academic and emotional well-being. Educational institutions should aim to increase the accessibility and visibility of such services, ensuring they meet the diverse needs of students. Future research should focus on quantitatively examining the direct impact of psychosocial support on academic outcomes to validate these findings further.